2005
DOI: 10.1016/j.cell.2005.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of p53 Translation and Induction after DNA Damage by Ribosomal Protein L26 and Nucleolin

Abstract: Increases in p53 protein levels after DNA damage have largely been attributed to an increase in the half-life of p53 protein. Here we demonstrate that increased translation of p53 mRNA is also a critical step in the induction of p53 protein in irradiated cells. Ribosomal protein L26 (RPL26) and nucleolin were found to bind to the 5' untranslated region (UTR) of p53 mRNA and to control p53 translation and induction after DNA damage. RPL26 preferentially binds to the 5'UTR after DNA damage, and its overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
657
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 606 publications
(681 citation statements)
references
References 55 publications
21
657
2
1
Order By: Relevance
“…This is different from what we observe in mammalian cells but it well illustrates how cell-typespecific factors tightly control translation of the p53 message. It has also been reported that p53 itself can mediate control of its own synthesis through interaction with its 5 0 UTR (Mosner et al, 1995) and a recent publication reports that the 5 0 UTR is responsible for mediating translation control of p53 after g-irradiation (Takagi et al, 2005). This could indicate that regions within the coding domain as well as within the 5 0 UTR mediate different types of stress-dependent translation control of p53 synthesis.…”
Section: Discussionmentioning
confidence: 96%
“…This is different from what we observe in mammalian cells but it well illustrates how cell-typespecific factors tightly control translation of the p53 message. It has also been reported that p53 itself can mediate control of its own synthesis through interaction with its 5 0 UTR (Mosner et al, 1995) and a recent publication reports that the 5 0 UTR is responsible for mediating translation control of p53 after g-irradiation (Takagi et al, 2005). This could indicate that regions within the coding domain as well as within the 5 0 UTR mediate different types of stress-dependent translation control of p53 synthesis.…”
Section: Discussionmentioning
confidence: 96%
“…We first investigated several reported candidate mRNAs, including BcL-xL, TNF-a,GADD45a, HOXA2, IER3 and p53 (Iervolino et al, 2002;Takagi et al, 2005;Yugami et al, 2007). Among them, only Bcl-xL and TNF-a cytosolic mRNA were found to be decreased on ActD treatment (data not shown).…”
Section: B23 Binds To Hnrnpu and Hnrnpa1 In The Cytosol In Response Tmentioning
confidence: 99%
“…These interactions suppress Mdm2 E3 ligase activity against the degradation of p53 protein. Moreover, rpL26 was identified as a p53 translational activator as it can bind the 5 0 -UTR of p53 mRNA and increase translation (Takagi et al, 2005). In contrast to the above described ribosomal proteins, there is another association between ribosomal protein (rpL26) and Mdm2 that differently regulates p53 protein level.…”
Section: Introductionmentioning
confidence: 99%